Dual information processing: Dissociation of type 1 and type 2 processes - Maceina, Tomas (Psichologija, 2015)
The last decade marks the rapid development of dual process theories of higher cognition (Evans, 2007; Evans & Stanovich, 2013 a; 2013 b), i. e. defining the features of intuitive Type 1 and reflective Type 2 processing were separated from their typical correlates, the consensus regarding the use of terminology was reached, and empirical research stimulated the creation of various models of the dual process of conflict resolution. Nevertheless, there is still little knowledge about the general principles of operation of the intuitive Type 1 and the reflective Type 2 processing. Particularly little attention is directed towards the question of interaction between both kinds of processing and their manifestation in a given information processing cycle. The main reason behind this problem is of methodological nature. To date, there are very few methods that both can address this issue and do it in the ecologically valid manner. The most promising model to deal with the aforementioned problem is process dissociation (Jacoby, 1991; Lindsay & Jacoby, 1994), however its use has been thwarted due to the unfavourable historical circumstances. During the period of 1991/1994–2006, the use of the process dissociation method has no firm theoretical basis, because the main principles of dual process theories (and particularly default-interventionist model) were still under discussion, while during the period of 2007–2015, cognitive psychologists used a less ecologically valid form of process dissociation method, which dubiously presupposes the priority of Type 2 processing, although the default-interventionist model highlights the priority of Type 1 processing. This article examines the possibilities of applying the process dissociation method in the context of contemporary dual process theories of higher cognition. It is concluded that the combination of two methods (process dissociation and counterintuitive tasks) may serve as a promising universal research strategy to analyze and mathematically evaluate the interaction of the intuitive Type 1 and the reflective Type 2 processing.